Verifying genetic diagnoses: Hereditary hemorrhagic telangiectasia – juvenile polyposis syndrome (HHT-JPS) or familial adenomatous polyposis (FAP)? - Mitchell Wagner; Alexander Beke; Harry Wilton-Clark; Sergio Zepeda-Gomez; Dilini Vethanayagam (Clinical and Investigative Medicine, 2026)
Abstract A 26-year-old woman was diagnosed with hereditary hemorrhagic telangiectasia – juvenile polyposis syndrome (HHT-JPS) after an incidental finding of a pulmonary arteriovenous malformation. Molecular genetic testing confirmed the presence of a pathogenic SMAD4 variant, later found to be present in several other family members who were all previously labelled as having familial adenomatous polyposis. This short report contrasts and compares the conditions and highlights the importance of using genetic testing to distinguish similar presentations of gastrointestinal polyps in association with genetic conditions such as HHT-JPS and FAP. We highlight that detection of SMAD4 mutations can distinguish individuals with HHT-JPS from those with FAP who do not appear to present with arteriovenous malformations or notable criteria for HHT. This distinction may have significant implications for those with a longstanding familial diagnosis of FAP, as HHT-JPS entails different management considerations.